Role of Inflammasomes in Kidney Diseases via Both Canonical and Non-canonical Pathways - Xiang, Huiling; Zhu, Feng; Xu, Zhifeng; Xiong, Jing (Frontiers in Cell and Developmental Biology, 2020)
Inflammasomes, multiprotein complex induced by harmful factors in the body, play a crucial role in innate immunity. Activation of inflammasomes lead to the activation of casepase-1 and then the secretion of inflammatory cytokines, including IL-1β and IL-18, subsequently leading to a type of cell death called pyroptosis. There are two types of signaling pathways involved in the process of inflammasome activation: the canonical and the non-canonical signaling pathway. The canonical signaling pathway is mainly dependent on casepase-1; the non-canonical signal pathway, which was recently discovered, is mainly dependent on caspase-11, but is also meditated by caspase-4, caspase-5 and caspase-8. Kidney inflammation is basically associated with inflammatory factor exudation and inflammatory cell infiltration. Several studies have showed that inflammasomes are closely related to kidney diseases, especially the NLRP3 inflammasome, which play a role in regulating kidney inflammation and fibrosis. In this review, we focus on the relationship between inflammasomes and kidney diseases, especially the role of the NLRP3 inflammasome in different kinds of kidney disease via both canonical and non-canonical signal pathways.